Wind power plants protection using overcurrent relays - Rezaei, Nima; Othman, Mohammad Lutfi; Abdul Wahab, Noor Izzri; Hizam, Hashim; Olufemi, Osaji Emmanuel (Horizon Research Publishing, 2014)
Wind power plants are one of the most crucial types of renewable energies which are increasingly employed in smart grids with purpose of power generation especially as a distribution generation system. Hence, the proper protection of wind plants is an enormously significant aspect which must be taken into consideration when designing the wind plants to not only provide a suitable protection for the power components but also maintain the power generation perpetually in case of fault. The most important and common protection systems are overcurrent relays which can protect the power systems from impending faults. In order to implement a successful and proper protection for wind power plants, these relays must be set accurately and well coordinated with each other to clear the fault at the system in the shortest possible time. This paper demonstrates how the coordination of overcurrent relays can be successfully achieved in wind power plants in order to maintain the power generation during fault and protect the power components.